An assessment of effluent treatment to reduce heavy metal levels in effluent from a battery manufacturing concern - Muleya, Eddwina; Chiumira, F. (RSC Publishing, 2016)
The study area is one of the point water pollution sources for chemical waste because this is a battery manufacturing concern. The city of Gweru is currently not monitoring the heavy metal levels in industrial waste, except for biological oxygen demand and pH. Heavy metals are bio-accumulative and hence are a health threat to humans, and to microorganisms and aquatic life in general. The battery manufacturing concern uses both borehole water and tap water in its processes. In this study, borehole. Water was also analysed in order to assess whether pollution at the surface was percolating downwards. Tap water was used as a control because the dam from which municipal water is drawn lies in an area far removed from pollution sources.